Comparison of Clinical Outcomes with Initial Norepinephrine or Epinephrine for Hemodynamic Support After Return of Spontaneous Circulation. Issue 6 (December 2021) - Weiss, Ashley; Dang, Cathyyen; Mabrey, Danielle; Stanton, Matthew; Feih, Jessica; Rein, Lisa; Feldman, Ryan
ABSTRACT: Background: The optimal vasoactive agent for management of patients with return of spontaneous circulation (ROSC) after cardiac arrest has not yet been identified. The Advanced Cardiac Life Support guidelines recommend initiation of either norepinephrine (NE), epinephrine (EPI), or dopamine (DA) to maintain adequate hemodynamics after ROSC is achieved. The goal of this study is to retrospectively assess the impact of initial vasopressor agent on incidence rate of rearrest, death, or need for additional vasopressor in post-cardiac arrest emergency department (ED) patients. Methods: A retrospective review of electronic medical records was conducted at a tertiary care, academic medical center over a 32-month period. Inclusion criteria were any patient who received vasopressors in the ED after achieving ROSC from out-of-hospital cardiac arrest, or in ED cardiac arrest. The incidence of the primary outcome was assessed during care within the ED, at 6 h regardless of location (early resuscitation period), and throughout the entire hospitalization. Secondary outcomes included incidence of tachyarrhythmia while on vasopressor, type of additional therapy needed for refractory shock, and functional status at discharge as determined by discharge location (discharged home without assistance, or discharged to long-term care facility, subacute rehabilitation, or assisted living). Results: A total of 93 patients were included for analysis; 45 received NE, 42 EPI, and six DA. Due to small sample size, DA was excluded from reporting post hoc. Significantly more EPI patients met the primary outcome of refractory hypotension, rearrest, or death in the emergency department (EPI 21/42, 50% vs. NE 10/45, 22.2%; P = 0.008). The incidence was no longer significantly different during the early resuscitation period of 6 h (EPI 30/42, 71.4% vs. NE 25/45, 55.6%; P = 0.182), or during the entire hospitalization (EPI 40/42, 95.2% vs. NE 36/45, 80.0%; P = 0.051). Notably, the EPI group had higher rates of rearrest prior to vasopressor initiation, potentially signaling more severe illness despite other prognostic variables being similarly distributed. In an adjusted regression model, which included adjustment for rearrest prior to vasopressor initiation, the odds of reaching the primary outcome in the ED were 3.94 [95%CI 1.38–12.2] ( P = 0.013) times higher in the EPI group compared to NE treated patients. No difference in tachyarrhythmia or functional status at discharge was detected between groups. Conclusion: These data suggest prospective study of initial vasopressors used for hemodynamic support after ROSC may be warranted. Rates of intra-emergency department refractory shock, rearrest, or death were higher among epinephrine treated patients compared to norepinephrine treated patients in this population. However, inability to control for potential confounding variables in retrospective studies limits the findings. These results are hypothesis generating and further study is warranted.